Fresh Waters and Fish Diversity: Distribution, Protection and Disturbance in Tropical Australia - Januchowski-Hartley, Stephanie R.; Pearson, Richard G.; Puschendorf, Robert; Rayner, Thomas (PLOS ONE, 2011)
Background Given the globally poor protection of fresh waters for their intrinsic ecological values, assessments are needed to determine how well fresh waters and supported fish species are incidentally protected within existing terrestrial protected-area networks, and to identify their vulnerability to human-induced disturbances. To date, gaps in data have severely constrained any attempt to explore the representation of fresh waters in tropical regions. Methodology and Results We determined the distribution of fresh waters and fish diversity in the Wet Tropics of Queensland, Australia. We then used distribution data of fresh waters, fish species, human-induced disturbances, and the terrestrial protected-area network to assess the effectiveness of terrestrial protected areas for fresh waters and fish species. We also identified human-induced disturbances likely to influence the effectiveness of freshwater protection and evaluated the vulnerability of fresh waters to these disturbances within and outside protected areas. The representation of fresh waters and fish species in the protected areas of the Wet Tropics is poor: 83% of stream types defined by order, 75% of wetland types, and 89% of fish species have less than 20% of their total Wet Tropics length, area or distribution completely within IUCN category II protected areas. Numerous disturbances affect fresh waters both within and outside of protected areas despite the high level of protection afforded to terrestrial areas in the Wet Tropics (>60% of the region). High-order streams and associated wetlands are influenced by the greatest number of human-induced disturbances and are also the least protected. Thirty-two percent of stream length upstream of protected areas has at least one human-induced disturbance present. Conclusions/Significance We demonstrate the need for greater consideration of explicit protection and off-reserve management for fresh waters and supported biodiversity by showing that, even in a region where terrestrial protection is high, it does not adequately capture fresh waters.